Strengthening Accessibility and Inclusivity in Libraries: The Role of Adaptive Technology in Supporting Visually Impaired Users - Wahyu Purnomo, Gabriel; Rizki Wikandani, Prayoga; Suprapto, Agung (Yayasan Adra Karima Hubbi, 2024)
Background. Libraries are essential in democratizing access to knowledge and information, but users with visual impairments still face significant barriers in accessing these resources. Purpose. This research explores how adaptive technologies can improve accessibility and inclusivity in libraries for users with visual impairments. Method. Using a qualitative methodology involving in-depth interviews and content analysis of library websites, this study assessed the effectiveness of current adaptive technologies and identified barriers to their use. Results. The findings show that, although adaptive technologies such as screen readers and indoor navigation systems hold great potential to improve user experience, there remains a lack of implementation and insufficient awareness among library staff regarding the specific needs of visually impaired users. Conclusion. The study emphasizes the importance of holistic integration of adaptive technologies in library service strategies to ensure equal access. Recommendations include better staff training, the development of solid and inclusive policies, and collaboration with disabled people's organizations to enhance library accessibility and inclusiveness, thereby supporting broader social participation of visually impaired users.